2012
DOI: 10.4049/jimmunol.1200497
|View full text |Cite
|
Sign up to set email alerts
|

A GpC-Rich Oligonucleotide Acts on Plasmacytoid Dendritic Cells To Promote Immune Suppression

Abstract: Short synthetic oligodeoxynucleotides (ODNs) rich in CpG or GpG motifs have been considered as potential modulators of immunity in clinical settings. In this study, we show that a synthetic GpC-ODN conferred highly suppressive activity on mouse splenic plasmacytoid dendritic cells, demonstrable in vivo in a skin test assay. The underlying mechanism involved signaling by noncanonical NF-κB family members and TGF-β–dependent expression of the immunoregulatory enzyme IDO. Unlike CpG-ODNs, the effects of GpC-ODN r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
3
25
1
Order By: Relevance
“…Moreover our data indicate that (d) immunostimulant activity by lower-dose CpG requires, instead, the TLR9-MyD88 pathway as well as production of the proinflammatory cytokine IL-23; (e) genetic deficiency of MyD88 negates functional effects by lower-dose CpG, implying that direction of response depends upon ligand ARTICLE concentration, which likely affects the affinity with which TLR9 recruits downstream adaptor and signalling molecules, including TRAF3 and TRAF6; (f) the protective effects of CpG in experimental allergy in vivo require a TLR9-TRIF circuit but not MyD88-dependent events. Not secondarily, we also confirmed that (g) a non-CpG ODN with two GpC motifs is exclusively immunosuppressive in the same setting, an effect we have recently demonstrated not to require TLR9 and be, in fact, contingent on TLR7-and TRIF-dependent signalling events 10 . As a corollary, a role, per se, of the phosphorothioate backbone in the TLR7 (GpC-dependent) and TLR9 (higher-dose CpG-dependent) pathways of tolerogenesis is ruled out by the stimulatory effect of lower-dose CpG on the same backbone, which is in line with the dual effects both of CpG on a phosphodiester backbone and of bacterial DNA.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Moreover our data indicate that (d) immunostimulant activity by lower-dose CpG requires, instead, the TLR9-MyD88 pathway as well as production of the proinflammatory cytokine IL-23; (e) genetic deficiency of MyD88 negates functional effects by lower-dose CpG, implying that direction of response depends upon ligand ARTICLE concentration, which likely affects the affinity with which TLR9 recruits downstream adaptor and signalling molecules, including TRAF3 and TRAF6; (f) the protective effects of CpG in experimental allergy in vivo require a TLR9-TRIF circuit but not MyD88-dependent events. Not secondarily, we also confirmed that (g) a non-CpG ODN with two GpC motifs is exclusively immunosuppressive in the same setting, an effect we have recently demonstrated not to require TLR9 and be, in fact, contingent on TLR7-and TRIF-dependent signalling events 10 . As a corollary, a role, per se, of the phosphorothioate backbone in the TLR7 (GpC-dependent) and TLR9 (higher-dose CpG-dependent) pathways of tolerogenesis is ruled out by the stimulatory effect of lower-dose CpG on the same backbone, which is in line with the dual effects both of CpG on a phosphodiester backbone and of bacterial DNA.…”
Section: Discussionsupporting
confidence: 67%
“…4b). (As expected 10 , under the same experimental conditions, the tolerogenic effects of GpC required neither TLR9 nor MyD88, Fig. 4b.)…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations